Orientation Feature Transform Model for Image Retrieval in Sketch Based Image Retrieval System - Prasad K, Durga; K, Manjunathachari; Prasad M.N, Giri (International Journal of Engineering and Technology, 2018)
This paper focus on Image retrieval using Sketch based image retrieval system. The low complexity model for image representation has given the sketch based image retrieval (SBIR) a optimal selection for next generation application in low resource environment. The SBIR approach uses the geometrical region representation to describe the feature and utilize for recognition. In the SBIR model, the features represented define the image. Towards the improvement of SBIR recognition performance, in this paper a new invariant modeling using â€œorientation feature transformed modelingâ€ is proposed. The approach gives the enhancement of invariant property and retrieval performance improvement in transformed domain. The experimental results illustrate the significance of invariant orientation feature representation in SBIR over the conventional models.Â Â